The Utility of Circulating and Imaging Biomarkers Alone and in Combination in Heart Failure - Jaltotage, Biyanka; Dwivedi, Girish; Ooi, Daryl E. L.; Mahadavan, Gnanadevan (Current Cardiology Reviews, 2021)
Clinical trials in the treatment of heart failure have relied on the use of a composite of hard clinical endpoints to evaluate the efficacy of the treatment arm. This has led to prolonged trials requiring large patient cohorts and extensive funding to reach statistical significance. In this paper, we have explored the potential of currently available circulating and imaging biomarkers associated with heart failure as a surrogate for hard clinical end points in clinical trials. This would be expected to result in shorter trials, smaller patient cohorts and limited funding required. We have subsequently theorized on combining circulating and imaging biomarkers as a surrogate for clinical end points such as hospitalization from heart failure and cardiac mortality.
Keywords: ECG